Etude et analyse d’un système photovoltaïque - Abdallah BOULARES; Mohamed Amine GUERRIB (My University, 2023)
Solar energy is one of the most important types of renewable energy that everyone today seeks to harness optimally due to its numerous advantages for the environment, economy, and sus- tainable development. Algeria's Sahara receives significant solar radiation throughout the year with very high intensity at its surface. In this thesis, we presented an analytical study and simulations of a solar system in the SONEL- GAZ Company in Souk-Ahras. The system is connected to the grid to provide a power of ap- proximately 19 KWC. The simulation results obtained through the PV SYSTM software were perfectly compatible with the theoretically obtained results. Key words: solar energy, solar radiation, grid connected system, PVSystem ----------------------------------------------------------------------------------------- الطاقة الشمسية هي واحدة من أهم أنواع الطاقة المتجددة التي يهتم الجميع حاليًا بالاستفادة منها بشكل مثلى نظرًا لمزاياها العديدة للبيئة والاقتصاد والتنمية المستدامة. يتلقى صحراء الجزائر تشعيعًا شمسيًا هائلاً طوال العام مع درجات حرارة عالية جدًا على سطحها . في هذا البحث، قمنا بتقديم دراسة تحليلية ومحاكاة لنظام الطاقة الشمسية لشركة سونلغاز سوق أهراس. يتصل النظام بالشبكة لتوفير طاقة قدرها 19 كيلو وات تقريبًا. أظهرت نتائج المحاكاة بواسطة برنامج PV SYSTM توافقًا مثاليًا مع النتائج التي تم الحصول عليها نظريً ----------------------------------------------------------------------------------------- L’énergiesolaireestl’undestyped’énergierenouvelablelesplusimportantsquetoutlemondetient aujourd’hui à l’exploitée de manière optimale en raison de ses nombreux avantages pourl’environnement,économieet développements durable . Le Sahara de l’Algérie reçoit une énergie de rayonnement solaire importante pendant toutl’année avecunetoustrèsélevésàsasurface. Dans ce mémoire, nous avons présenté une étude analytique et simulations de système solairedel’entreprisedeSONELGAZSouk-Ahras . Le système connecté au réseau pour fournir une énergie de 19 KWC presque les résultats desimulation par le logiciel PV SYSTM ont été parfaitement compatible au résultat obtenusthéoriquement.